Anti-beta1-adrenergic receptor autoantibodies in patients with chronic Chagas heart disease - Labovsky, Vivian (2007)
Chronic Chagas heart disease (cChHD), a chronic manifestation of the Trypanosoma cruzi infection, is characterized by high antibody levels against the C-terminal region of the ribosomal P proteins (i.e. peptide R13, EEEDDDMGFGLFD) which bears similarity with the second extracellular loop of beta1-adrenergic receptor (beta1-AR, peptide H26R HWWRAESDEARRCYNDPKCCDFVTNR). Because it has not been demonstrated clearly that IgGs from cChHD patients bind to native human beta1-AR, the aim of this study was to investigate further the physical interaction between cChHD IgGs and the human beta1-AR. Immunofluorescence assays demonstrated the binding of these antibodies to the receptor expressed on stably transfected cells, together with a beta1-AR agonist-like effect. In addition, immunoadsorption of the serum samples from cChHD patients with a commercially available matrix, containing peptides representing the first and the second extracellular loop of the beta1-AR, completely abolished reactivity against the H26R peptide and the physiological response to the receptor. The follow-up of this specificity after in vitro immunoadsorption procedures suggests that this treatment might be used to diminish significantly the serum levels of anti-beta1-AR antibodies in patients with Chagas heart disease.